THE EFFECT OF REMUNERATION AND WORK DISCIPLINE ON THE PERFORMANCE OF MEMBERS OF THE NATIONAL POLICE UNIT OF THE SAMAPTA DIRECTORATE OF NORTH SULAWESI POLICE - Erika Kaunang; Merinda Pandowo (Universitas Sam Ratulangi, 2024)
This study aims to determine the remuneration and work discipline on the performance of members of the National Police Unit of the Samapta Directorate of North Sulawesi Police. Remuneration Variable is tested using 4 indicators, Work Discipline Variable uses 7 indicators, and Employee Performance Variable is tested using 7 indicators. This research methodology uses purposive sampling The research approach used in this study is a comparative quantitative method. The sampling technique used was with an infinite population and a sample of 86 respondents. In determining the sample size in this study is based on the determination of samples developed by Rosque. Data collection techniques are carried out by making observations to the field and distributing respondent questionnaires, using multiple linear regression. The calculation result is obtained that the calculated value is greater than the table value. So Ho is rejected and Ha is accepted, which means that Remuneration and Work Discipline have a significant effect on employee performance. Keywords: remuneration, work discipline, performance